A retrospective analysis for investigating the relationship between FIGO stage IVA/IVB and cytoreductive surgery with prognosis in epithelial ovarian cancer - Liu, Hong; Luo, Min; Peng, Chunrong; Huang, Jianmei; Wang, Dengfeng; Huang, Jianming; Zhang, Guonan (Frontiers in Oncology, 2023)
Objective To investigate the effect of primary debulking surgery (PDS), NACT followed by interval debulking surgery (NACT-IDS), and chemotherapy alone on the prognosis of FIGO stage IV epithelial ovarian cancer (EOC) with different metastatic patterns. Methods We retrospectively analyzed 133 cases of FIGO stage IV EOC with pleural effusion (stage IVA), parenchymal metastases (stage IVB), or extra-abdominal lymph node metastases (stage IVB) at our Hospital between January 2014 and July 2021. Results Among 133 cases with stage IV disease, 16.5% (n=22) presented with pleural effusion, 46.6% (n=62) with parenchymal metastases, and 36.9% (n=49) with extra-abdominal lymph node metastases. Regardless of the metastatic patterns, the 90.2% (n=120) of cases who underwent PDS/NACT-IDS exhibited a significantly superior overall survival (OS) compared to the 9.8% cases (n=13) who received chemotherapy alone (32 vs 17 months, p=0.000). The cohort was further stratified into 58 cases (48.3%) with R0, 41 cases (34.2%) with R1, and 21 cases (17.5%) with R2. The median OS of cases with R0 was significantly better than that of cases with R1/R2 (74 vs 27 months, p=0.000). There was no significant difference in median OS between PDS and NACT-IDS (43 vs 31 months, p=0.676), as well as between FIGO IVA and IVB (35 vs 31 months, p=0.582). Additionally, the metastatic patterns and the number of neoadjuvant chemotherapy cycles (≤4 or >4) did not demonstrate any prognostic significance for median OS (p=0.820 and 33 vs 26 months, p=0.280, respectively). Conclusion Regardless of FIGO IVA and IVB stages or metastatic patterns, patients diagnosed with stage IV EOC may benefit from cytoreductive surgery with abdominal R0, compared with chemotherapy alone.